The Influence of Profitability, Company Size, and Growth Opportunity on the Quality of Profits in Property and Real Estate Companies Listed on The Indonesian Stock Exchange (BEI) Year 2019-2022 - WIDJAYANTI, Putu Feby Silvia; SAPUTRA, Komang Adi Kurniawan; LARASDIPUTRA, Gde Deny (Journal of Governance, Taxation and Auditing, 2024)
The importance of this research is that profit imbalance causes the company's profit quality to decline. If the quality of the company's profits decreases, it will cause errors in decision-making by users of financial reports. This study looks at the link between a firm's size, profitability, growth potential and the quality of its profits. All real estate and property firms listed on the Indonesia Stock Exchange between 2019 and 2022, whose financial reports are available to the public, comprise the research population. Saturated sampling is the sampling strategy employed in this investigation. The study sample comprised sixty-one real estate and property businesses on the Indonesia Stock Exchange (BEI). A total of 244 samples were used in the investigation during the four years. Data analysis approaches employed in this study included multiple linear analysis, hypothesis testing, classical assumption testing, and descriptive statistics. According to the study's findings, profitability significantly and favorably affects the quality of earnings; the size of the business significantly and favorably affects the quality of earnings, and growth opportunities somewhat but favorably affect the quality of earnings.